Phenomenological approach in exploring the roles of youth citizen journalists in Malaysia - Mahamed, Mastura (2018)
Citizen journalism has been increasingly embraced among citizens globally with the expansion of the internet, new media technologies and social media platforms. In Malaysia, most studies about Malaysian citizen journalism were concentrated around Malaysian political scene and the elections. However not many studies were done to uncover who are the citizen journalists, their roles of these people behind citizen journalism or citizen reporting Malaysians particularly among youth segment of the population. The aim of this study is to explore the roles of youth citizen journalists in Malaysia. The study explored and applied the Produsage Theory with its adapted model of Motivational, Situational and Social factors shaping productive news use. Another theory used to explore the study is the Conversational Concept which would help further explain the iterative cycle of self-production and use (interaction) in playing their role as citizen journalists. The study was conducted in various cities in Malaysia precisely in Klang Valley, Johor Bahru, Kota Bharu, and Kuala Terengganu. The selection of informants was based on purposive sampling. They were from youth category (15-40 year old) Malaysians from multiple races. They also should at least attend formal education in Malaysia with various family, cultural background and education level. The informants were gathered from Citizen Journalists Malaysia (CJ.MY), The Vocket and The Patriots. These informants maintain their independent as citizen journalist though they have preferred platform based on their preference and interests. 14 informants participated in the study. Qualitative inquiry using the phenomenology approach was selected to capture as much depth of the informant’s experience. In depth interview and observation was chosen as the data collection strategies to allow depth and rich data possible. Atlas.ti 8 was used to analyze the data that eventually create emerging themes. Audit trail,members check, peer examination and rich thick description were used to ensure reliability and validity of the study. The results of the study revealed, the informants saw youth citizen journalism with potential for citizens to express themselves. The informants also see it as empowerment for youth as well as for them to position themselves as important in the society. The citizen journalists also determined the traits of citizen journalist accordingly based on their personal experience. They often identify themselves playing more than just information distributors. They really take their role seriously with the association of responsibility and for the benefit of others. Therefore, the importance of spreading knowledge with adequate fact checking was consistent outcome of the journalistic process and ethical considerations. The evidence of life experiences also influenced their decision to become youth citizen journalists. In conclusion, the themes emerged displayed similarities of elements that ultimately represent the attempt to answer the research objectives in exploring their role and depth of meaning of citizen journalism phenomenon among youth in Malaysia.